Prevalence of cell phone use while driving in different urban settings. A roadside observational study in maputo city, Mozambique - Alfredo Júlio Maposse; Lucie Laflamme; Franziska Fischer; Jette Möller (Heliyon)
Introduction: All forms of cell phone use while driving poses a threat to traffic safety. Few studies have reported the prevalence from low- and middle-income countries where the risk of severe road traffic crashes is highest. This study aimed to ascertain the prevalence of cell phone use among motor vehicle drivers in Maputo city, Mozambique, considering different types of vehicles and cell phone use. Methods: A roadside observational study was conducted to assess cell phone use while driving in three typical urban environments (on straight roads, at intersections, and by roadside markets) during three daytime periods. The prevalence of use, expressed in percentages with 95 % confidence intervals, was estimated by type of vehicle and sex. Results: An overall 9.3 % prevalence of cell phone use was observed among the 11 680 completed observations of motor vehicle drivers. Prevalence was lower at intersections and by roadside markets (7.1 % respective 7.5 %) and higher on straight roads (12.9 %) and, for men, three times as high among car drivers (10.3 %) than among drivers of motorized three-wheelers (3.3 %). Speaking/listening was more prevalent than texting/reading for both women (52.6 % vs 36.1 %) and men (46.4 % vs 40.5 %). At all three types of sites, men in trucks spoke/listened more than men in other type of vehicles while men in cars texted/read to a greater extent. Conclusion: The overall prevalence of cell phone use observed among motor vehicle drivers in Maputo city is in the upper range of those observed in high-income settings. Notwithstanding sex-related differences and variations by type of site and vehicle and coupled with the poor road safety conditions of the city – and of the country as a whole – and the imminent rise in cell phone ownership and internet connectivity, cell phone use at the wheel is a significant cause for concern and concerted actions are called for.